Corrosion-resistant austenitic stainless steel for spent fuel aftertreatment and preparation method of corrosion-resistant austenitic stainless steel

By designing austenitic stainless steel with specific element ratios and using ultrapure smelting and thermal machining processes, the intergranular corrosion problem of austenitic stainless steel in nitric acid medium in spent fuel post-treatment is solved, and nitric acid is realized at high temperature The low corrosion rate and excellent welding performance in the process meet the material needs of spent fuel after treatment.

CN119320914APending Publication Date: 2025-01-17INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411337813.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing domestic commercial austenitic stainless steel is prone to intergranular corrosion in nitric acid medium in special environments of spent fuel post-treatment, which cannot meet the harsh and complex corrosion environment requirements. In addition, international developed countries block the technology of nuclear materials, which affects my country's nuclear power. Sustainable development.

Method used

The weight percentage is 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤ 0.05, austenitic stainless steel with a margin of Fe and inevitable impurity elements is prepared by ultrapure purification smelting, thermal machining and solid solution treatment to form excellent intergranular corrosion resistance.

Benefits of technology

In the special after-treatment environment containing spent fuel radioactive ions and halogen, the material does not undergo intergranular corrosion in boiling and high-temperature nitric acid, the corrosion rate is lower than the design requirements, meets service safety requirements, and has excellent welding and processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005058773810000071
    Figure BDA0005058773810000071
  • Figure HDA0005058773820000011
    Figure HDA0005058773820000011
  • Figure HDA0005058773820000012
    Figure HDA0005058773820000012
Patent Text Reader

Abstract

The invention relates to corrosion-resistant austenitic stainless steel for spent fuel aftertreatment and a preparation method of the corrosion-resistant austenitic stainless steel, belongs to the field of nuclear materials and technologies, and solves the key problem that existing domestic commercial austenitic stainless steel is prone to intergranular corrosion in a nitric acid medium in a special spent fuel aftertreatment environment. The stainless steel comprises the following components in percentage by weight: 15.0 to 20.0 percent of Cr, 12.0 to 18.0 percent of Ni, 3.0 to 6.0 percent of Si, 0.05 to 2.0 percent of Mn, 0.05 to 2.0 percent of W and Mo, 0.20 to 0.20 percent of N, 0.20 to 0.20 percent of Nb and V, 0.05 to 0.05 percent of rare earth element RE and the balance of Fe and inevitable impurity elements: less than or equal to 0.010 percent of C, less than or equal to 0.005 percent of P, less than or equal to 0.005 percent of S, less than or equal to 0.005 percent of O and less than or equal to 0.005 percent of B. The preparation method of the stainless steel comprises the steps of vacuum induction melting, vacuum consumable remelting, thermal machining and solution treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to corrosion-resistant austenitic stainless steel for spent fuel post-processing and a preparation method thereof, belonging to the field of nuclear materials and technology. Background Art

[0002] At present, the back-end treatment of spent fuel cycle is the weakest link in my country's nuclear energy system. Under the complex service conditions of post-processing, the materials used must meet the following performance requirements at the same time: (1) Resistance to corrosion by special medium solutions. The temperature of nitric acid solution can reach up to boiling, and the concentration can reach 6 mol / l or even higher in some places. More importantly, the mixing of oxidizing metal ions (such as chromium, ruthenium, and cadmium ions) and halogen elements in spent fuel into nitric acid solution will significantly change the corrosion behavior of the material, leading to severe intergranular corrosion and pitting, and greatly increasing the corrosion rate, thus affecting service safety. In addition, in addition to the corrosion of liquid nitric acid, the material may also face corrosion from gaseous and condensed reflux nitric acid. According to the service conditions, the design proposes that the corrosion resistance index of the material is: after the intergranular corrosion test is carried out according to the C method of GB / T4334-2020 (14.4mol / L boiling nitric acid for a total of 240h), no intergranular corrosion occurs and the corrosion rate is ≤0.60mm / a (millimeter / year), and under the simulated post-processing conditions (95℃, 6mol / L, nitric acid containing oxidizing metal ions and halogens), no intergranular corrosion occurs and the annual corrosion rate after immersion until the corrosion rate stabilizes is ≤0.30mm / a. (2) Excellent comprehensive mechanical properties such as tensile, impact and fatigue. (3) Weldable. The components need to be connected by welding, and the corrosion resistance of the welded joint is not lower than the design requirements of the parent material. (4) It can be prepared and processed by engineering. Small-scale preparation in the laboratory cannot meet the requirements of engineering, and the material does not crack during engineering preparation and processing. (5) Relatively low cost.

[0003] Research on post-processing materials mainly focuses on Zr alloys, Ti-Ta alloys and low-carbon stainless steel. Although Zr and Ti alloys have excellent resistance to nitric acid corrosion, they are expensive and difficult to process. Low-carbon 304L austenitic stainless steel is a commonly used material in the nitric acid industry and post-processing fields, but it is prone to severe intergranular corrosion in nitric acid solutions containing oxidizing ions above about 70°C. 310L austenitic stainless steel, which has good corrosion resistance in the nitric acid chemical industry, has a low corrosion rate and excellent intergranular corrosion resistance in pure nitric acid, but the addition of oxidizing ions and halogens in high-temperature nitric acid will also lead to intergranular corrosion. Therefore, the existing commercially mature austenitic stainless steel cannot meet the harsh and complex corrosion environment requirements of post-processing.

[0004] Internationally developed countries have imposed a strict blockade on my country in terms of key nuclear materials and technologies. Therefore, in order to ensure the sustainable development of my country's nuclear power, accelerate the processing capacity of nuclear fuel, and meet the growing demand for spent fuel processing, it is urgent to develop corrosion-resistant austenitic stainless steel for spent fuel reprocessing with China's independent intellectual property rights. Summary of the invention

[0005] (I) Purpose of the invention

[0006] The purpose of the present invention is to provide a corrosion-resistant austenitic stainless steel for spent fuel post-processing and a preparation method thereof, so that the stainless steel has excellent intergranular corrosion resistance in a nitric acid solution containing radioactive ions and halogens in a special post-processing environment of spent fuel, and is intended to be used as a material for key components of spent fuel post-processing, thereby solving the key problem that the existing domestically produced commercial austenitic stainless steel is prone to intergranular corrosion in a nitric acid medium in a special post-processing environment of spent fuel.

[0007] (II) Technical solutions to be adopted to solve the problem:

[0008] A corrosion-resistant austenitic stainless steel for spent fuel reprocessing, wherein the stainless steel has the following components, measured by weight percentage: 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤0.05, the balance being Fe and unavoidable impurity elements, the impurity elements being: C≤0.010, P≤0.005, S≤0.005, O≤0.005, and B≤0.005.

[0009] The method for preparing the corrosion-resistant austenitic stainless steel for spent fuel reprocessing comprises the following steps:

[0010] (1) Ultra-pure smelting: The alloy is prepared by vacuum induction melting and vacuum consumable arc melting in a dual process, and the riser and surface oxide scale of the smelting ingot are removed;

[0011] (2) Thermomechanical processing: The ingot is subjected to hot forging and / or hot rolling processing. The holding temperature before processing is 1100-1250°C and the holding time is ≥12h; the hot forging / rolling temperature range is 850°C-1250°C, and the ingot is air-cooled to room temperature after hot processing;

[0012] (3) Solution treatment: The solution treatment temperature is 1000-1250°C, the holding time is 0.1-5 hours, and then rapid cooling is performed. The cooling rate in the range of 500-800°C is ≥50°C / min.

[0013] The preparation method of the corrosion-resistant austenitic stainless steel for spent fuel reprocessing has a delta ferrite content of ≤1%; inclusions A, B, C, D and Ds are all ≤0.5 level; no intergranular corrosion occurs in a pure nitric acid solution with a temperature of ≤95°C and a concentration of ≤6 mol / L, and the corrosion rate after immersion until the corrosion rate is stable is ≤0.10 mm / a; no intergranular corrosion occurs in a nitric acid solution with a temperature of ≤95°C and a concentration of ≤6 mol / L containing oxidizing ions, and the corrosion rate after immersion until the corrosion rate is stable is ≤0.30 mm / a; in the C method intergranular corrosion experiment according to GB / T4334-2020, immersion in a 14.4 mol / L boiling pure nitric acid solution for 5 cycles for a total of 240 hours, no intergranular corrosion occurs, and the corrosion rate is ≤0.50 mm / a.

[0014] The design principles and purposes of the important elements of the austenitic stainless steel of the present invention are as follows:

[0015] (1) C: ≤0.010%

[0016] Ultra-low carbon (C) is one of the most critical designs for the intergranular corrosion resistance of austenitic stainless steel of the present invention. Generally, C is one of the important alloying elements in steel. However, during heat treatment or welding, C in steel easily forms carbides M at the grain boundaries. 23 C 6 (M is mainly Cr), resulting in intergranular Cr deficiency and intergranular corrosion. Therefore, in order to obtain excellent intergranular corrosion resistance, C is set to be controlled at ≤0.010%, preferably ≤0.005%.

[0017] (2) Si: 3.0% to 6.0%

[0018] The addition of an appropriate amount of Si is the second key design of the corrosion resistance of austenitic stainless steel of the present invention. In low-carbon austenitic stainless steels with excellent corrosion resistance, such as 304L or 310L, Si exists as an impurity element and its content is controlled to be less than 1%. In the present invention, Si is one of the important alloying elements for nitric acid corrosion resistance, and its purpose is to form a silicate passivation film in a high-temperature nitric acid solution containing radioactive ions and halogens to protect the substrate from intergranular corrosion. However, too low a content of Si is insufficient to form a protective film, while too high a content of Si will affect the welding performance and processing performance of the material.

[0019] (3) Cr: 15% to 20%

[0020] Cr is an indispensable alloying element for ensuring the conventional corrosion resistance of stainless steel, and its content is generally ≥12%. For example, the Cr content in 316 and 314 austenitic stainless steels is generally 16%. However, when the Cr content is too high, such as exceeding 20%, a Cr-rich brittle phase is easily formed. In addition, too high Cr tends to promote the formation of ferrite, resulting in the appearance of austenite-ferrite dual-phase structure in the material, which in turn reduces the nitric acid corrosion resistance. The present invention optimizes the Cr content while adding Si, forming a silicate and Cr-rich double-layer passivation film structure, thereby improving the intergranular corrosion resistance.

[0021] (4) Ni: 12% to 18%

[0022] Ni is an element required to obtain austenite structure and inhibit intergranular corrosion. Ni can also reduce the work hardening rate during cold deformation. If the Ni content is too low, a stable austenite structure cannot be obtained. If the content is too high, the material price will be more expensive. In addition, Ni is prone to transmutation reaction to produce He under strong neutron irradiation, resulting in radiation swelling, etc., and is not suitable for large-scale addition in the spent fuel reprocessing environment.

[0023] (5)N: ≤0.2%

[0024] In conventional pure nitric acid solution and halogen elements (such as Cl - ) In nitric acid, austenitic steel is prone to pitting corrosion in addition to intergranular corrosion. N is one of the elements that improves the pitting corrosion resistance of steel. At the same time, the addition of an appropriate amount of N also has certain benefits on the hot working properties of the material. The present invention will achieve precise control of the addition and content of N by adding an intermediate alloy such as CrN.

[0025] (6) Rare earth elements: ≤0.05%

[0026] Adding a small amount of rare earth elements to the steel is also a key design for the corrosion resistance of the austenitic stainless steel of the present invention. The purpose is to further reduce the impurity content in the steel based on the high chemical affinity of rare earth with O and S, purify the grain boundaries, and change the morphology of inclusions (such as MnS), thereby improving the corrosion resistance and mechanical properties of the material.

[0027] (7) S, P: ≤0.005%

[0028] The segregation of elements such as S and P at the grain boundaries is the second main cause of intergranular corrosion in austenitic stainless steel. In addition, S and P are also likely to increase the crack sensitivity of the heat-affected zone of welding. Generally, the S and P content in steels with higher performance requirements is controlled to be ≤0.03%. However, the present invention has more stringent requirements on corrosion resistance, so the S and P content is required to be controlled to ≤0.005%, preferably ≤0.001%.

[0029] The austenitic stainless steel of the present invention has the following advantages and beneficial effects:

[0030] (1) In order to achieve the above-mentioned key performance requirements of excellent corrosion resistance, the austenitic stainless steel of the present invention is designed in terms of composition: a) strictly controlling C≤0.010% to eliminate the Cr content of conventional austenitic steel. 23 C 6 The first major factor leading to intergranular sensitization is precipitation. b) Adding an appropriate amount of Si and synergistically optimizing the Cr and Ni contents, by forming a dense double-layer passivation film of silicate and Cr oxide, protects the matrix from high temperature and corrosion by nitric acid containing strong oxidizing ions. c) Adding an appropriate amount of rare earth elements changes the morphology of inclusions and improves purity, and strictly controls the S and P contents to avoid intergranular corrosion caused by grain boundary segregation. d) Adding an appropriate amount of N content improves the material's pitting resistance and hot working properties.

[0031] (2) In order to achieve the above-mentioned excellent corrosion resistance, welding performance and processing performance requirements, the austenitic stainless steel of the present invention adopts the following preparation process: a double process of vacuum induction melting and vacuum consumable arc melting is adopted to obtain a high purity material with inclusion level ≤0.5; a high temperature and long-term heat preservation treatment is performed before hot processing to improve the uniformity of material composition and structure and eliminate the segregation of delta ferrite structure and Si; and a high cooling rate in the sensitizing temperature zone during the solution treatment is controlled to further inhibit intergranular sensitization. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Metallographic microstructure photographs of Example 1: (a) grain morphology; (b) inclusions.

[0033] Figure 2 Microstructure metallographic photographs of Comparative Example 1: (a) grain morphology; (b) delta ferrite.

[0034] Figure 3 Microstructure metallographic photographs of Comparative Example 2: (a) grain morphology; (b) inclusions.

[0035] Figure 4 SEM photos of the corrosion surface morphology of Example 1, Comparative Example 1 and Comparative Example 2: (a) Example 1; (b) Comparative Example 1; (c) Comparative Example 2. (Immersion corrosion test conditions: boiling, 14.4 mol / L pure nitric acid, corrosion time 240 h).

[0036] Figure 5 SEM photos of the corrosion surface morphology of Example 1, Comparative Example 1 and Comparative Example 2: (a) Example 1; (b) Comparative Example 1; (c) Comparative Example 2. (Immersion corrosion test conditions: 95°C, 6 mol / L, nitric acid containing oxidizing ions, corrosion time 5472h). DETAILED DESCRIPTION

[0037] The following examples will further illustrate the present invention, but are not intended to limit the present invention. The steels in the examples and comparative examples were subjected to purification smelting, homogenization treatment, hot working and solution treatment, and then tested to study their corrosion resistance.

[0038] The following is a detailed description in conjunction with the attached tables and drawings, which constitute a part of this application and are used together with the embodiments and comparative examples to illustrate the principles of the present invention.

[0039] Example 1

[0040] In this embodiment, the alloy composition of the austenitic steel is, by weight percentage (wt%): Cr: 15.5; Ni: 15.2; Mn: 1.5; Si: 4.1; Mo: 0.2; N: 0.05; Nb: 0.1; RE (lanthanum): 0.01; C: 0.008; O: 0.003; P: 0.005; S: 0.005; B: 0.001; the remainder is iron.

[0041] The preparation process of the austenitic stainless steel of the present invention is: batching → vacuum induction smelting → vacuum consumable arc smelting → hot forging → hot rolling → solution treatment, and the specific steps are as follows:

[0042] (1) High-purity raw materials are used and prepared according to the proportion of alloy elements. They are purified and smelted in a 200 kg vacuum induction furnace, and then vacuum consumable arc smelting and casting are performed to obtain steel ingots. The surface oxide scale is removed and the ingot riser is cut off.

[0043] (2) The ingot is hot forged in the austenite phase region at a holding temperature of 1250°C for 20 h; the starting forging temperature is 1200°C, the final forging temperature is 850°C, the forging ratio is about 5:1, and the ingot is air-cooled to room temperature after forging.

[0044] (3) The hot forged material is hot rolled, with the starting rolling temperature at 1200°C, the final rolling temperature at 850°C, the reduction in each rolling pass at 10%, the total deformation at 50%, and air cooling to room temperature after rolling.

[0045] (4) The rolled material is subjected to a solution treatment at a solution temperature of 1200°C for 2 hours and a water cooling method, wherein the cooling rate in the range of 500 to 800°C is approximately 110°C / min.

[0046] Example 2

[0047] In this embodiment, the alloy composition of austenitic steel is, by weight percentage (wt%): Cr: 17.5; Ni: 14.9; Mn: 1.0; Si: 3.8; Mo: 0.3; N: 0.15; V: 0.1; RE (yttrium): 0.008; C: 0.006; O: 0.004; P: 0.003; S: 0.005; B: 0.003; the remainder is iron.

[0048] The preparation process of austenitic stainless steel in this embodiment is the same as that in embodiment 1.

[0049] Comparative Example 1

[0050] In this comparative example, the alloy composition of the austenitic steel, measured in weight percentage (wt%), is: Cr: 15.8; Ni: 15.0; Mn: 1.6; Si: 3.9; Mo: 0.2; N: 0.48; RE (lanthanum): 0.01; Nb: 0.05; C: 0.009; O: 0.005; P: 0.005; S: 0.005; B: 0.005; the balance is iron.

[0051] In this comparative example, the N content is higher than that in Example 1.

[0052] The processing and preparation method of austenitic steel in this comparative example is basically the same as that in Example 1, except that the holding time before forging is only 2 hours.

[0053] Comparative Example 2

[0054] In this comparative example, the alloy composition of the austenitic steel is, by weight percentage (wt%): Cr: 25.1; Ni: 20.9; Mn: 0.24; Si: 0.11; Mo: 0.1; N: 0.55; C: 0.007; O: 0.008; P: 0.045; S: 0.03; the balance is iron.

[0055] Compared with the embodiment, the main differences in the composition of this comparative example 2 are: the Si content is lower and is controlled as an impurity element; the Cr, Ni and N contents are higher. The main components of this comparative example 2 are basically the same as those of 310L steel except that the N content is increased to 0.55wt%.

[0056] The processing and preparation process of the austenitic steel in this comparative example 2 is as follows: vacuum induction smelting and casting are used to obtain a steel ingot; the obtained steel ingot is forged in the austenite phase region, the initial forging temperature is about 1230°C, the forging ratio is greater than 5:1, and air-cooling is performed to room temperature after forging; the forged steel ingot is hot-rolled, the start rolling temperature is about 1180°C, the reduction amount for each rolling pass is controlled to be 10%, the total reduction amount is controlled to be 60%, and air-cooling is performed to room temperature after hot rolling; the plate is solution treated after hot rolling, the temperature is kept at 1200°C for 30 minutes, and then water quenched to room temperature.

[0057] Figure 1 This is the metallographic structure and inclusion analysis of the sample in Example 1. Figure 1 a shows that the material is a fully austenitic structure with a grain size of about 200 μm, and no delta ferrite is found. Figure 1 b shows that the material has high purity and the inclusion level is ≤0.5.

[0058] Figure 2 This is the metallographic structure of the sample of Comparative Example 1. Figure 2 a shows that the material is mainly austenite. However, due to the addition of 0.48wt% N, more precipitates or inclusions appeared in the matrix or grain boundaries, indicating that excessive addition of N is likely to form precipitates or inclusions and may be detrimental to intergranular corrosion resistance. In addition, Figure 2 b shows that due to the short holding time, the material still contains a small amount of delta ferrite, about 5 vol%.

[0059] Figure 3 a is the metallographic structure of comparative example 2, which is a fully austenitic structure. Compared with example 1, the grain size is finer, about 100 μm, indicating that the addition of 0.55 wt % N refines the grain size. Figure 3 b is the inclusion analysis of comparative example 2. Since the dual smelting process of vacuum induction and vacuum self-consumption is not performed, the S and P contents in the material are higher than those in the embodiment, resulting in more inclusions.

[0060] Corrosion tests were carried out on the materials of the examples and comparative examples under different conditions to study and evaluate the corrosion resistance of the materials. The annual corrosion rate calculated by corrosion weight loss is shown in Table 1, and its representative surface corrosion morphology is shown in Figure 4-Figure 5 .

[0061] According to the GB / T4334-2020C method, the intergranular corrosion experiment after the material sensitization treatment was carried out, that is, 5 cycles of corrosion in pure nitric acid with a boiling temperature of 123°C and a concentration of 14.4 mol / L for a total of 240 hours. As shown in Table 1, the corrosion rates of Example 1 and Example 2 are 0.48 mm / a and 0.47 mm / a, respectively, which are both less than the design requirement of 0.50 mm / a. The corrosion rate of Comparative Example 1 reached 2.1 mm / a, indicating that the increase of N content to 0.48 wt% on the basis of Example 1 significantly accelerated the corrosion of the material. Comparative Example 2 has the lowest corrosion rate, which is only 0.08 mm / a.

[0062] Figure 4 It is the surface corrosion morphology under corresponding corrosion conditions. Figure 4 a and Figure 4 c shows that the materials of Example 1 and Comparative Example 2 did not suffer from intergranular corrosion and pitting corrosion, indicating that they have intergranular corrosion resistance in boiling nitric acid. Figure 4As shown in b, obvious cracking occurred at the grain boundaries of the material of Comparative Example 1.

[0063] After reducing the nitric acid concentration to 6 mol / L and the temperature to 95°C and etching for 240 hours, the corrosion rates of the examples and comparative examples were greatly reduced, as shown in Table 1. At this time, the corrosion has reached a stable state, and the corrosion rates of Examples 1 and 2 are 0.08 mm / a and 0.07 mm / a, respectively, and the corrosion rate of Comparative Example 2 is 0.004 mm / a, both of which are less than 0.10 mm / a.

[0064] In actual service conditions, a variety of radioactive strong oxidizing ions will be mixed into the nitric acid solution. These ions will change the corrosion potential and corrosion behavior of austenitic stainless steel, thus significantly affecting the corrosion resistance of the material. Therefore, further corrosion tests were carried out in a simulated post-processing near-service environment. Oxidizing ions were added to 95°C, 6 mol / L nitric acid, and the corrosion test time was increased to 5472h.

[0065] Table 1 Annual corrosion rate of the materials of the embodiments and comparative examples after corrosion by nitric acid solution under different conditions

[0066]

[0067] Note: " / " is not tested.

[0068] The results in Table 1 show that although the corrosion rate of Example 1 is increased to about 0.25 mm / a compared with the pure nitric acid solution under the same conditions, it does not exceed the design index of 0.3 mm / a and meets the service requirements. However, the corrosion rates of Comparative Examples 1 and 2 increased significantly, both exceeding 0.3 mm / a.

[0069] Figure 5 is the surface corrosion morphology under the corresponding conditions. Figure 5 As shown in a, the surface of the sample in Example 1 is a typical uniform corrosion morphology, and no intergranular corrosion and pitting corrosion are observed, indicating that the material in Example 1 still has excellent intergranular corrosion resistance after long-term immersion under near-working conditions. Figure 5 b shows that the sample in Comparative Example 1 suffered severe intergranular corrosion. Figure 5 The comparative example 2 sample of c shows that although it has the lowest corrosion rate in boiling and 95°C pure nitric acid, its corrosion behavior in high-temperature nitric acid containing oxidizing ions changes significantly, and severe intergranular corrosion occurs.

[0070] The results of the embodiments and comparative examples show that when the main alloying elements of the present invention are Cr 15.5-17.5, Ni 14.9-15.2, Mn 1.0-1.5, Si 3.8-4.1, 0.1≤W+Mo≤0.3, N 0.05-0.10, 0.05≤Nb+V≤0.10, and RE0.008-0.01, no formation of delta ferrite is found in combination with a specific preparation method, and the inclusion grade is ≤0.5 grade; in 95°C, 6mol / L pure nitric acid, intergranular corrosion does not occur and the corrosion rate is ≤0.10mm / a; in 95°C, 6mol / L nitric acid that is post-treated with oxidizing ions, intergranular corrosion does not occur and the corrosion rate is ≤0.30mm / a; in 123°C, 14.4mol / L pure nitric acid, intergranular corrosion does not occur and the corrosion rate is ≤0.50mm / a. The corrosion-resistant austenitic stainless steel and the preparation method thereof are mainly used in the field of spent fuel post-processing, and can also be applied to the field of nitric acid chemical industry.

Claims

1. A corrosion-resistant austenitic stainless steel for spent fuel reprocessing, characterized in that: In terms of weight percentage, the composition of stainless steel is as follows: 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤0.05, the balance is Fe and unavoidable impurity elements, impurity elements: C≤0.010, P≤0.005, S≤0.005, O≤0.005, B≤0.

005.

2. A method for preparing the corrosion-resistant austenitic stainless steel for spent fuel reprocessing according to claim 1, characterized in that: The steps include: (1) Ultra-pure smelting: The alloy is prepared by vacuum induction melting and vacuum consumable arc melting in a dual process, and the riser and surface oxide scale of the smelting ingot are removed; (2) Thermomechanical processing: The ingot is subjected to hot forging and / or hot rolling processing. The holding temperature before processing is 1100-1250°C and the holding time is ≥12h; the hot forging / rolling temperature range is 850°C-1250°C, and the ingot is air-cooled to room temperature after hot processing; (3) Solution treatment: The solution treatment temperature is 1000-1250°C, the holding time is 0.1-5 hours, and then rapid cooling is performed. The cooling rate in the range of 500-800°C is ≥50°C / min.

3. The method for preparing corrosion-resistant austenitic stainless steel for spent fuel reprocessing according to claim 2, characterized in that: δ ferrite content ≤1%; inclusions A, B, C, D and Ds are all ≤0.5 level; no intergranular corrosion occurs in pure nitric acid solution with temperature ≤95℃ and concentration ≤6mol / L, and the corrosion rate after immersion until the corrosion rate is stable is ≤0.10mm / a; no intergranular corrosion occurs in nitric acid solution with temperature ≤95℃, concentration ≤6mol / L and containing oxidizing ions, and the corrosion rate after immersion until the corrosion rate is stable is ≤0.30mm / a; in the C method intergranular corrosion test according to GB / T4334-2020, it is immersed in 14.4mol / L boiling pure nitric acid solution for 5 cycles for a total of 240h, and intergranular corrosion does not occur and the corrosion rate is ≤0.50mm / a.

Citation Information

Cited By

  • Extra-thick austenitic stainless steel plate for fusion reactor loop pipeline and manufacturing and welding method

    CN121759822A

  • Super-thick austenitic stainless steel plate for fusion reactor circuit pipe, and manufacturing and welding method thereof

    CN121759822B